Different Vaccination Strategies for Measles Diseases: A Simulation Study (Journal of Informatics and Mathematical Sciences, 2011)
Vaccination strategies are designed and applied to control or eradicate an infection from the population. This paper studies three different vaccination strategies used world wide for many infectious diseases including measles. These strategies are the conventional constant vaccination strategy, the periodic step (pulse) vaccination strategy and finally the mixed vaccination strategy of both the constant and the periodic one. Simulation of the different vaccination programs is been conducted. The Poincaré section is playing as a filter of our simulation results to show a wide range of possible behavior of our model. critical vaccination parameter is been estimated from the results to prevent sever epidemics.
Keywords: Simulation; SEIR model; Periodic vaccination; Poincaré section; Filter; Epidemics